2001
DOI: 10.1016/s1074-5521(01)00061-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel enzyme activities and functional plasticity revealed by recombining highly homologous enzymes

Abstract: Permutation of nine amino acid differences resulted in a set of enzymes with surprisingly diverse patterns of reactions catalyzed. The functional richness of this small area of sequence space may aid our understanding of both natural and artificial evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 31 publications
5
64
0
2
Order By: Relevance
“…It has also been observed that the dehalogenase AtzA is closely related to TriA, an enzyme that catalyzes deamination reactions (58). It was further shown in the laboratory that two amino acid changes are sufficient to evolve TriA, which is not appreciably active in dehalogenation, into an enzyme with significant dehalogenase activity (51). These two amino acid changes are present in the naturally occurring AtzA enzymes that have been sequenced to date (61).…”
Section: S-triazine Metabolism and Genesmentioning
confidence: 98%
See 1 more Smart Citation
“…It has also been observed that the dehalogenase AtzA is closely related to TriA, an enzyme that catalyzes deamination reactions (58). It was further shown in the laboratory that two amino acid changes are sufficient to evolve TriA, which is not appreciably active in dehalogenation, into an enzyme with significant dehalogenase activity (51). These two amino acid changes are present in the naturally occurring AtzA enzymes that have been sequenced to date (61).…”
Section: S-triazine Metabolism and Genesmentioning
confidence: 98%
“…AtzA shows an astounding 98% amino acid sequence identity to melamine deaminase, an enzyme that was not observed to catalyze appreciable dechlorination (61). The natural evolution of a deaminase to a dechlorinase was recapitulated by laboratory directed-evolution experiments that identified the key amino acid residues changing the activity into a dechlorinase (51). A similarly close relative of TrzN has not been identified.…”
Section: Enormous Metabolic Versatility From Three Catabolic Genes Anmentioning
confidence: 99%
“…Another intermediate technique is ''directed evolution,'' in which new microbial genes are selected from mixtures of DNA fragments in laboratory cultures. Directed evolution has been used to breed bacteria that are better at degrading pesticides and other environmental pollutants and to breed viruses for biological control (e.g., Soong et al 2000, Raillard et al 2001, Sakamoto et al 2001). Since organisms modified by this method use only natural recombination, albeit under artificial conditions, regulatory agencies do not consider them to be ''genetically engineered.…”
Section: Techniques For Creating Transgenic Organismsmentioning
confidence: 99%
“…2C). This hypothesis was supported by directed evolution experiments in which atzA and triA genes were shuffled to generate clonal variants with one or a few amino acid changes and with differential leaving group specificities in displacement from the s-triazine ring (47). It was proposed that a change in an aspartate (TriA) to an asparagine (AtzA) was important in its evolution into a dehalogenase (48).…”
Section: Minireview: Evolution Of Microbial Enzymes 41260mentioning
confidence: 99%